Energy Materials - Bruce, D; O'Hare, D; Walton, R (John Wiley and Sons, 2011)
In an age of global industrialisation and population growth, the area of energy is one that is very much in the public consciousness. Fundamental scientific research is recognised as being crucial to delivering solutions to these issues, particularly to yield novel means of providing efficient, ideally recyclable, ways of converting, transporting and delivering energy. This volume considers a selection of the state-of-the-art materials that are being designed to meet some of the energy challenges we face today. Topics are carefully chosen that show how the skill of the synthetic chemist can be applied to allow the targeted preparation of inorganic materials with properties optimised for a specific application. © 2011 John Wiley and Sons, Ltd.